U–Pb and Re–Os Geochronology of the Hucunnan Copper–Molybdenum Deposit in Anhui Province, Southeast China, and its Geological Implications. Issue 3 (9th June 2016) - Yang, Heming; Du, Yangsong; Lu, Yinghuai; Chen, Linjie; Zheng, Zejun; Zhang, Yun
Abstract: The Middle–Lower Yangtze Region (MLYR) is one of the most important metallogenic belts in China that hosts numerous Cu–Fe–Au–S deposits. The Hucunnan deposit in the central part of MLYR is a newly discovered porphyry–skarn‐type copper–molybdenum deposit during recent drilling exploration. Laser ablation ICP–MS analysis carried out in this study yields U–Pb isotopic ages of 137.5 ± 1.2 Ma for the Cu–Mo bearing granodiorite rock and 125.0 ± 1.5 Ma for the Cu‐bearing quartz diorites. The Re–Os isotopic dating of seven molybdenite samples gave an isochron age of 139.5 ± 1.1 Ma, suggesting a syn‐magma mineralization of molybdenite in the Hucunnan deposit. Since porphyry‐type molybdenum deposits are rare in central MLYR, the discovery of the Hucunnan deposit suggests possible molybdenite mineralizations in the deep places of the Cu–Mo bearing granitoids. In addition, the U–Pb isotopic age of 125 Ma for the Cu‐bearing quartz diorites implies a new Cu mineralization period for the MLYR that was rarely reported by previous studies. Abstract : The Hucunnan deposit in the central part of The Middle‐Lower Yangtze Region is a newly discovered copper‐molybdenum deposit during recent drilling exploration. In this study, Two episodes of magma activates have been recognized. The first episode (137.5±1.2) Ma formed the Cu‐Mo bearing granodiorite rock, while the second (125.0±1.5 Ma) generated the Cu‐bearing quartz diorites.